PERAN BADAN MUSYAWARAH KAMPUNG DALAM PENGAWASAN KINERJA PEMERINTAH KAMPUNG IFIA-FIA - Syabana, Rifai Nur; Ohoiwutun, Yosephina; Muhdiarta, Untung; Aedah, Nur; Sapioper, Hiskia C.M.; Renyaan, Dorthea (JURNAL KEBIJAKAN PUBLIK, 2026)
Supervision of village governance is an important aspect in achieving accountability and transparency. The Village Consultative Body (Bamuskam) has a strategic role in supervising the performance of the Village Government, particularly in the stages of planning, implementation, and reporting. However, in practice, this role has not yet been optimally carried out in Ifia-Fia Village, Arso Barat District, Keerom Regency. This study aims to analyze the role of Bamuskam in supervising the performance of the Ifia-Fia Village Government and to identify the factors influencing the implementation of such supervision. This research uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observation, and documentation involving informants from Bamuskam members, village government officials, and the community. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings show that the supervisory role of Bamuskam has not been optimally implemented. In the planning stage, supervision has not been effective due to the absence of Village Deliberation as a key stage, resulting in the failure of preliminary supervision. In the implementation stage, supervision remains individual, not institutionally coordinated, and not comprehensive. Meanwhile, in the reporting stage, supervision has not been conducted due to the absence of accountability reports, evaluation forums, and adequate feedback mechanisms. The influencing factors include limited human resource capacity, insufficient understanding of regulations, low community participation, and unstable village governance conditions. Thus, it can be concluded that Bamuskam supervision has not been effective, systematic, and sustainable in supporting accountable, participatory, and transparent village governance.